Professional Learning Implementation and Challenges in rural Schools in Sambas District - Dedi Irwan (IKIP PGRI Pontianak, 2020)
This study aimed to describe the implementation of professional learning practices and their challenges , based on the rural schools’ perspective. The result of this study was expected to provide description of the how far has the activities of professional learning been applied by school and what challenges they face in implementing the activities. This research was multiple case study conducted using a descriptive qualitative approach involving 4 rural schools in Sambas Regency, particularly in Sebawi and Tebas sub-districts. Tool of data collection used was interview guidance, and the data analysis technique applied were thematic and cross case analyses techniques. The result of this study showed that professional learning practices had been implemented in different level. In addition, a number of challenges which constrained schools in implementing the professional learning practices had been identified